Register to donate while you wait: Assessing public opinions of the acceptability of utilizing the emergency department waiting room for organ and tissue donor registration. Issue 5 (September 2019) - Ellis, Brittany; Hartwick, Michael; Perry, Jeffrey J.
ABSTRACT: Objective: Our objectives were to identify barriers to the organ donation registration process in Ontario; and to determine the acceptability of using the emergency department (ED) waiting room to provide knowledge and offer opportunities for organ and tissue donor registration. Methods: We conducted a paper based in-person survey over nine days in March and April 2017. The survey instrument was created in English using existing literature and expert opinion, pilot tested and then translated into French. Data was collected from patients and visitors in an urban academic Canadian tertiary care ED waiting room. All adults in the waiting room were approached to participate during study periods. We excluded patients who were too ill and required immediate treatment. Results: The number of attempted surveys was 324; 67 individuals (20.7%) declined participation. A total of 257 surveys were distributed and five were returned blank. This gave us a response rate of 77.8% with 252 completed surveys. The median age group was 51–60 years old with 55.9% female. Forty-six percent reported their religion as Christian and 34.1% did not declare a religious affiliation. 44.1% were already registered donors. Most participants agreed or were neutral that the ED waiting room was an acceptable place to provide information on donation, and for registration as an organ and tissue donor (83.3% and 82.1%, respectively). Conclusions: Individuals waiting in the ED are generally supportive of using the waiting room for distributing information regarding organ and tissue donation, and to allow donor registration. Résumé: Contexte: L'étude avait pour objectifs : 1) de relever les obstacles au processus d'inscription du don d'organes en Ontario; 2) de déterminer l'acceptabilité sociale de l'utilisation de la salle d'attente du service des urgences (SU) comme lieu de diffusion de l'information sur les dons de matériel biologique, et d'inscription de donneurs d'organes et de tissus. Méthode: Une enquête a été menée en personne, au moyen d'un questionnaire sur papier, durant 9 jours, en mars et en avril 2017. L'instrument d'enquête a d'abord été élaboré en anglais à l'aide de la documentation existante et de l'avis d'experts, puis soumis à un essai pilote avant d'être traduit en français. La collecte de données s'est faite parmi les patients et les personnes qui les accompagnaient dans une salle d'attente d'un SU d'enseignement, de soins tertiaires, situé en milieu urbain, au Canada. Tous les adultes présents dans la salle d'attente ont été invités à participer à l'étude durant la période en question. Ont été exclus les patients qui étaient trop malades ou dont l'état nécessitait des soins immédiats. Résultats: Il y a eu 324 demandes d'enquête et 67 personnes (20, 7%) ont refusé de participer. Sur un total de 257 questionnaires remis, 5 ont été rendus vierges, ce qui a porté à 77, 8% (252 questionnaires remplis) le taux de réponse. L'âge médian était de 51–60 ans, et 55, 9% des répondants étaient des femmes. Quarante-six pour cent des participants se sont déclarés chrétiens et 34, 1% n'ont rien indiqué quant à leur appartenance religieuse; par ailleurs, 44, 1% étaient déjà des donneurs inscrits. La plupart des répondants se sont montrés favorables ou neutres à l'égard de l'utilisation de la salle d'attente du SU comme lieu de diffusion de l'information sur les dons de matériel biologique, ou d'inscription de donneurs d'organes et de tissus (83, 3% et 82, 1%, respectivement). Conclusion: Dans l'ensemble, les personnes interrogées au SU se sont montrées favorables à l'utilisation de la salle d'attente comme lieu de diffusion de l'information sur les dons d'organes et de tissus, et d'inscription de donneurs.